The Impact of Digital Tools on Students’ Artistic Competencies in Fine Arts Education - Muzafarova Sanobar Murodullayevna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article examines the influence of digital tools on the development of students’ artistic competencies in fine arts education. It highlights how software applications, virtual studios, and interactive learning platforms enhance students’ creative thinking, compositional skills, and aesthetic judgment. The study emphasizes the integration of digital technologies with interactive pedagogical methods, including project-based learning and collaborative activities, to foster both individual and group creativity. Additionally, the article analyzes the teacher’s role in guiding and motivating students to effectively use digital tools to maximize their artistic potential.